The Role of Motivation on Performance with Competence as a Moderation Variable in Financial Personnel - Rahayu, Sri Bekti (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the role of motivation on performance with competence as a moderation variable in financial personnel. Motivation plays an important role in improving performance, especially in a work environment that requires high accuracy and dedication, such as in the financial field. Competencies are assumed to strengthen the relationship between motivation and performance, as adequate abilities and skills allow individuals to work more effectively and efficiently. This study uses a quantitative approach with a survey method involving financial personnel as respondents. The data were analyzed using moderation regression analysis to test the relationships and interactions between the variables. The results showed that motivation had a significant positive role in performance, and competence significantly moderated the relationship. These findings have practical implications for the development of training programs and strategies to increase motivation among financial personnel